Grzebień znaleziony w studni ludności kultury przeworskiej z miejscowości Konotopa na Mazowszu - Machajewski, Henryk (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Excavations carried out in advance of the construction of A-2 highway in the vicinity of the village of Konotopa unearthed the settlement site of the Przeworsk culture which functioned between the late phase B2 until the second half of phase C2. The site produced a number of interesting finds, including a three-layer comb representing type I, variety 1 according to S. Thomas, dated to the second half of phase C2 of the Late Roman Iron Age.
Comb from a Przeworsk Culture well from Konotopa in Mazovia